Mechanical Stability of Calcium Alginate Liquid Core Capsules - Muhammad Ismat Arif Mohd Nordin (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To investigate the effect of concentration of the gelling agents and the gel thickness of the capsules. To determine the mechanical strength of capsules produced under different ranges of the process variables. To develop a mathematical model correlate the effect of process variables on the gel.